Predictors of Cognitive Decline in Older Adult Type 2 Diabetes from the Veterans Affairs Diabetes Trial - Zimering, Mark B.; Knight, Jeffrey; Ge, Ling; Bahn, Gideon, the VADT Investigators; Soule, Jeremy; Caulder, Susan; Pittman, Clare; Alston, Omayra; Mayfield, Ronald K.; Moffitt, Greg; Sagel, Julius; et al. (Frontiers in Endocrinology, 2016)
Aims: Cognitive decline disproportionately affects older adult type 2 diabetes. We tested whether randomized intensive glucose-lowering reduces the rate(s) of cognitive decline in adults with advanced type 2 diabetes (mean: age, 60 years; diabetes duration, 11 years) from the Veterans Affairs Diabetes Trial. Methods: A battery of neuropsychological tests (digit span, digit symbol substitution (DSym), and Trails-making Part B (TMT-B)) was administered at baseline in 1700 participants and repeated at year 5. Thirty-six risk factors were evaluated as predictors of cognitive decline in multivariable regression analyses. Results: The mean age-adjusted, DSym or TMT-B declined significantly in all study participants (P < 0.001). Randomized intensive glucose-lowering did not significantly alter the rate of cognitive decline. The final model of risk factors associated with 5-year decline in age-adjusted TMT-B included as significant predictors: longer baseline diabetes duration (beta = -0.028; P = 0.0057), lower baseline diastolic blood pressure (beta = 0.028; P < 0.001), and baseline calcium channel blocker medication use (beta = -0.639; P < 0.001). Higher baseline pulse pressure was significantly associated with decline in age-adjusted TMT-B suggesting a role for both higher systolic and lower diastolic blood pressure. Baseline thiazide diuretic use (beta= -0.549; P =0.015) was an additional significant predictor of 5-year decline in age-adjusted digit symbol score. Post-baseline systolic blood pressure-lowering was significantly associated (P < 0.001) with decline in TMT-B performance. There was a significant inverse association between post-baseline plasma triglyceride- lowering (P = 0.045) and decline in digit symbol substitution task performance. Conclusions: A five-year period of randomized intensive glucose-lowering did not significantly reduce the rate of cognitive decline in older-aged adults with type 2 diabetes. Systolic and diastolic blood pressure as well as plasma triglycerides were modifiable risk factors of the rate of cognitive decline in older adult type 2 diabetes.